SOME ASPECTS REGARDING SOCIAL SERVICES FOR PEOPLE WITH DISABILITIES (PANGEEA, 2025)
Most of the time, people with special needs were hidden from the eyes of the world through institutions, and no one knew what was going on there or they were kept in the shadows within their own family. These individuals had no rights, no obligations, no facilities and thus their essential rights were violated among those provided for in the Constitution. Currently, more than one billion people suffer from a certain type of disability, and global trends such as an aging population and global growth in chronic health conditions show that there is an increase in the prevalence of disability. This is due to an aging population and an increased risk of disability among the elderly as well as a global increase in chronic health conditions such as diabetes, cardiovascular disease, cancer and mental illness. Poor health, poorer educational performance, lower economic strength and high poverty are aspects that require increased effort on the part of people with disabilities. Since the entry into force of the United Nations Convention on the Rights of Persons with Disabilities, the focus has been on: ways to combat discrimination, promote accessibility and inclusion, and especially on increasing respect for people with disabilities.
Keywords: authority; person with disability; solutions; protection; legislation